The rising swarms of jellyfish in Indian waters: the environmental drivers, ecological, and socio-economic impacts. Issue 10 (20th October 2022) - Siddique, Alfisa; Purushothaman, Jasmine; Madhusoodhanan, Rakhesh; Raghunathan, Chelladurai
Abstract: A four-decade data of jellyfish aggregation from 1980 to 2020 were taken to discern whether there has been an actual rise in jellyfish swarm in Indian coastal and estuarine waters. Despite frequent jellyfish aggregations and beach strandings in Indian waters, jellyfish aggregations have been poorly investigated and there is a dearth of information on the swarm-forming jellyfish, their preferred season, and the location of swarming. Therefore, our review aims to account for the frequency of swarming phenomenon annually and the appearance of new swarm-forming jellyfish species. The term 'jellyfish' refers to the medusae stage of phylum Cnidaria (Cubozoa, Hydrozoa, and Scyphozoa) only in this review. The present work postulates a geospatial spread and swarm-forming jellyfish species to increase in recent times. More than 23 coastal locations of India have witnessed jellyfish aggregations and beach stranding in the last four decades. Seasonal oceanographic conditions prevailing during the summer monsoon, fall, and early winter promoted jellyfish aggregations and swarming. Only two jellyfish species were known to form aggregates during 1981–1990, but the diversity of jellyfish species increased to nine by 2011–2020. The development of predictive models from remote sensing data can be useful to warn humans and coastal industries of the approaching swarm. HIGHLIGHTS: Geospatial spread, frequency of jellyfish swarms, and the number of swarm-forming species increased in the coastal and estuarine waters of India. More than 23 locations along the coast of India have witnessed jellyfish aggregations, swarms, and beach stranding in the last four decades. Seasonal oceanographic conditions during the summer monsoon, fall, and early winter promote jellyfish aggregations. Graphical Abstract